Pola Pewarisan di Kalangan Nelayan Desa Pandanganwetan, Kecamatan Kragan, Kabupaten Rembang - Agus Sudaryanto (Fakultas Hukum Universitas Gadjah Mada, 2009)
The aim of this research is to find out empirical data about inheritance pattern of fisherman in Pandangan Wetan, Kragan, Rembang village. This way, the development of inheritance problem among the Javanish society become to be known. Data collection was carried out by library and field research. The library research has been done as the guidance for the field research and analysis intensified. Subjects of the research are determined by purposive sampling and field data are collected by interview method. There are 18 respondents (ships owner and labor) and 5 key informants (head village, village secretary, TPI leader, youth leader and religious figure) in this research. The data from library and field research were analysed qualitatively. The result of this research indicates that the inheritance pattern of fisherman performed by before and after a person who leaves an inheritance death. There are differencies on the heritage distribution pattern among male and female children on the rich and the poor fisherman. The rich fisherman who has numerous property will give their heritage to male and female children but the poor fisherman tend to give their heritage to female child priority.